Literacy Improvement Through Regional Libraries in Maros Regency - Darmawati (Indonesian Journal of Society Development, 2023)
The author carries out this service activity with the aim of providing education to increase literacy to the visitors to the Maros Regency regional library. In addition, the author also contributed several anthology books with other author friends. This began when he received an assignment letter from the campus and then communicated with the management of the Maros Regency Regional Library. After being accepted, the author came to provide education in the form of brainstorming with visitors about the importance of increasing literacy. Because at that time there was still a Covid-19 pandemic, visitors were still limited, generally only students and students who were still in the online learning process. The educational process with visitors was not carried out simultaneously, but came one by one at the reading table. The author conveys material about the importance of increasing literacy, supporting and inhibiting factors for increasing literacy, solutions to overcome problems of increasing literacy. In addition, the author also prepared several short story anthology books to be shown and discussed to the visitors. After the implementation was completed, the Short Story Anthology book was handed over to the manager of the Regional Library of Maros Regency. This community service activity was carried out in May - July 2021 at the Regional Library of Maros Regency